The Hysteresis Performance and Restoring Force Model for Corroded Reinforced Concrete Frame Columns - Guifeng Zhao; Meng Zhang; Yaoliang Li; Dawang Li (Journal of Engineering)
A numerical simulation of the hysteresis performance of corroded reinforced concrete (RC) frame columns was conducted. Moreover, the results obtained were compared with experimental data. On this basis, a degenerated three-linearity (D-TRI) restoring force model was established which could reflect the hysteresis performance of corroded RC frame columns through theoretical analysis and data fitting. Results indicated that the hysteretic bearing capacity of frame columns decreased significantly due to corrosion of the rebar. In view of the characteristics of the hysteresis curve, the plumpness of the hysteresis loop for frame columns decreased and shrinkage increased with increasing rebar corrosion. All these illustrated that the seismic energy dissipation performance of frame columns reduced but their brittleness increased. As for the features of the skeleton curve, the trends for corroded and noncorroded members were basically consistent and roughly corresponded to the features of a trilinear equivalent model. Thereby, the existing Clough hysteresis rule can be used to establish the restoring force model applicable to corroded RC frame columns based on that of the noncorroded RC members. The calculated skeleton curve and hysteresis curve of corroded RC frame columns using the D-TRI model are closer to the experimental results.